What's Gaby cooking. Take it easy : recipes for zero stress deliciousness - Dalkin, Gaby, 1986- (Abrams, 2022)
In her new book, Gaby Dalkin returns with her signature approach: Enjoy your life by eating the food you love. But this time around, she also emphasizes a no-fuss attitude. What's Gaby Cooking: Take It Easy offers 100 new delicious and stress-free recipes, suited for any and all occasions.